The influence of the crystallization temperature on the reliability of PbTiO3 thin films prepared by chemical solution deposition. Issue 4 (April 2017) - Ali, H. El Hosiny; Ricote, J.; Calzada, M.L.; Bretos, I.; Jiménez, R.
Abstract: The preparation of quality ferroelectric PbTiO3 (PT) thin films at the lowest possible temperature preserving its functional properties is necessary for their integration in microdevices. The crystallization below, close or above the para-ferrolectric transition temperature of the PbTiO3 must produce an important effect on the microstructure, texture and residual stress state of the films and on functional properties. In this paper, the Chemical Solution Deposition method has been used to prepare PbTiO3 films at different temperatures around that of the ferroelectric to paraelectric phase transition. The films were analyzed by X-ray diffraction, Optical and Scanning Electron Microscopy, and their microstructure, texture and residual stress correlated with their functional properties. The results show that these PT films prepared with crystallization temperatures close or below the phase transition develop a favorable microstructure and texture that lead to high remnant and saturation polarization values, making them good candidates for their integration in microdevices.